Research Progress on the Structural Characteristics of Pumpkin Polysaccharide, Mechanism and Influencing Factors of Ameliorating Diabetes Mellitus - Yanan HAN; Xiaojuan LI; Xun WANG; Chunxu LENG; Xi ZHAO; Wei ZHAO; Jie LU; Zhugang LI (Shipin gongye ke-ji, 2024)
Polysaccharides are one of the most important natural bioactive ingredients in pumpkin. Pumpkin polysaccharides have variable structure and complex monosaccharide composition, and possess a variety of biological activities such as hypoglycemia and antioxidant. In recent years, with the increasing incidence of diabetes, the hypoglycemic effect of pumpkin polysaccharides has attracted more and more attentions of scholars. The research focuses on the structure, monosaccharide composition and different mechanism of action of pumpkin polysaccharides. Therefore, this paper systematically summarizes the structural characteristics, mechanisms of hypoglycemic action and influence factors of hypoglycemic activity of pumpkin polysaccharides, and looks forward to its research direction and application prospects, and proposes the suggestions, with a view to providing reference for the subsequent research of pumpkin polysaccharides on diabetes.